Accelerated Solvent Extraction of Terpenes in Cannabis Coupled With Various Injection Techniques for GC-MS Analysis - Myers, Colton; Herrington, Jason S.; Hamrah, Paul; Anderson, Kelsey (Frontiers in Chemistry, 2021)
The cannabis market is expanding exponentially in the United States. As state-wide legalization increases, so do demands for analytical testing methodologies. One of the main tests conducted on cannabis products is the analysis for terpenes. This research focused on implementation of accelerated solvent extraction (ASE), coupled with surrogate matrix matching, and an evaluation of traditional versus more modern sample introduction techniques for analyzing terpenes via gas chromatography – mass spectrometry (GC-MS). Introduction techniques included Headspace-Syringe (HS-Syringe), HS-Solid Phase Microextraction Arrow (HS-SPME Arrow), Direct Immersion-SPME Arrow (DI-SPME Arrow), and Liquid Injection-Syringe (LI-Syringe). The LI-Syringe approach was deemed the most straightforward and robust method with a terpene working range of 0.04 – 5.12 µg/mL; an average r2 of 0.993; an average LOQ of 0.049 µg/mL; an average analytical precision of 1.62% RSD; and an overall ASE-LI-Syringe-GC-MS method precision of 4.75% RSD for the 23 terpenes of interest. Sample workflows and results are discussed, with an evaluation of the advantages/limitations of each approach, and opportunities for future work.